Design and Implementation of a Dual Uncrewed Surface Vessel Platform for Bathymetry Research Under High-Flow Conditions - Dinesh Kumar; Amin Ghorbanpour; Kin Yen; Iman Soltani (IEEE Access)
Bathymetry, the study of underwater depth and topography, relies on detailed sonar mapping of the underwater structures. These measurements, critical for infrastructure health monitoring and hazard detection, often require prohibitively expensive sensory equipment and stable measurement conditions. The high financial risk associated with sensor damage or vessel loss creates a reluctance to deploy uncrewed surface vessels (USVs) for bathymetry. However, the alternative, crewed-boat bathymetry operations, are costly, pose significant hazards to personnel, and frequently fail to achieve the highly stable conditions necessary for bathymetry data collection, especially under challenging conditions such as high currents. Consequently, further research is essential to advance autonomous control, navigation, and data processing technologies, with a particular focus on bathymetry while ensuring safety under extreme conditions. There is a notable lack of accessible hardware platforms that allow for integrated research in both bathymetry-focused autonomous control and navigation, as well as data evaluation and processing. This paper addresses this gap by detailing the design and implementation of two complementary (dual) research USV systems tailored for uncrewed bathymetry research. This includes a low-cost USV for Navigation and Control research (NAC-USV) and a second, high-end USV equipped with a high-resolution multi-beam sonar and the associated hardware for Bathymetry data quality Evaluation and Post-processing research (BEP-USV). The NAC-USV facilitates the investigation of autonomous, fail-safe navigation and control technologies, emphasizing the stability requirements for high-quality bathymetry data collection while minimizing the risk to expensive equipment, allowing for seamless transfer of validated controls to the BEP-USV. The BEP-USV, which mirrors the NAC-USV hardware, is then used for additional control validation and in-depth exploration of bathymetry data evaluation and post-processing methodologies. We detail the design and implementation of both USV systems, open source hardware and software design, and the bill of material. Furthermore, we demonstrate the system’s effectiveness in both research and bathymetric applications across a range of operational scenarios. All the information are available at: https://github.com/Soltanilara/Twin-USV/